The efficacy of intralesional dexamethasone versus intravenous dexamethasone in surgery for impacted third molars: A randomized controlled trial - Agrawal, Amiya (Natl J Maxillofac Surg, 2020)
OBJECTIVES: A randomized prospective double-blind study was conducted to determine the efficacy of sub-mucosal local infiltration vs. intravenous dexamethasone in reducing postoperative pain, swelling and trismus after surgical removal of impacted mandibular third molars. MATERIALS AND METHODS: Forty five patients were included in the study and were randomly divided into three groups. Each group consisted of 15 patients for which the first and second groups were given 8 mg of dexamethasone intrlesionally & intravenously respectively, at 30 minutes prior to surgery; the third group served as control. Duration of facial swelling was evaluated subjectively by the patients themselves. Severity of postoperative pain was quantified by counting the number of analgesics taken by the patients during and after surgery (six subsequent days). Postoperative trismus was determined by measuring the maximum incisal opening before surgery and on the seventh day. RESULTS: Results showed that duration of postoperative edema was almost the same in the three test groups. During surgery, the intravenous dexamethasone group showed a significantly lesser pain than the other two groups; the intralesional dexamethasone group showed less marked pain than the control group. Additionally, patients who had taken steroids had a marked increase in the incisal opening postoperatively over the control group. Trismus was significantly reduced in the methylprednisolone group as compared to the dexamethasone group. CONCLUSION: It is concluded that both preoperative local infiltration and intravenous administration of dexamethasone significantly reduced postoperative pain and trismus after surgical removal of mandibular third molars. An intravenous dexamethasone is more effective in reducing postoperative inflammatory sequelae than its intralesional route.